Preserving the Local Wisdom of Sukowilangun Village through Cultural Rituals Towards a Cultural Heritage Tourism Village - Widayati, Sri; Setiyaningsih, Lian Agustina; Affandi, Arif Syaivul; Saputra, Alfarizi Dwi; Sufoyanto, Sufiyanto; Cahyaningsih, Diyah Sukanti (CV. Creative Tugu Pena, 2023)
The public service emphasizes cross-generational collaboration in Sukowilangun Village. The main aim to elevate cultural rituals in the form of birth, marriage and death rituals and “Jaranan” to become cultural heritage. One of the activities undertaken was pavilion flooring and the addition of important facilities has improved the quality of cultural workshops, increasing engagement, especially among the younger generation. In addition, documentation of cultural activities, such as the “Jaranan Turonggo Setyo Budoyo” dance, provides valuable insight into the community's cultural heritage, while emphasizing their commitment to preservation. The creation of a video documenting the project process showcases intergenerational collaboration and innovation, emphasizing the importance of upholding ancestral cultural values in society. Overall, this initiative not only preserves the local wisdom but also fosters unity and continuity. This underlines the potential of technology and collaboration in safeguarding cultural heritage and passing it on to future generations. The recommendation is to maintain a social media presence to increase external community awareness of the cultural product. Keywords: Local Wisdom, Cultural Rituals, Tourist Villages, Cultural Heritage, Jaranan